PERFORMANCE EVALUATION OF COMMUNITY MICROFINANCE INSTITUTIONS IN JEMBER DISTRICT - Wijayantini, Bayu; Sari, Maheni Ika; Arif, Alfi (Review of Management and Entrepreneurship, 2019)
Community Micro Finance Institution (CMFI) plays a significant role in alleviating poverty, which is the biggest problem in developing countries. This study aims to examine the phenomenon of CMFI development in Jember. This study is conducted using a descriptive statistical analysis and through literature study from literatures relevant to the research theme. The results of the study show that financial performance proxied by ROA has a different trend from total assets and government subsidies. ROA tends to decline even though there are some CMFIs that show good performance. This is contrary to the development of CMFI’s total assets which tend to increase throughout Jember, while government subsidies are still accepted in the same amount as intended from year to year.